DETERMINATION OF WEIBULL PARAMETERS FOR WIND APPLICATIONS IN TWO DIFFERENT REGIONS - Borges, W. F. A.; Araújo, A. M.; Oliveira Filho, O. D. Q. de; Rohatgi, J. S.; Pinto, G. F. (Revista de Engenharia Térmica, 2018)
In this work, the main objective is to determine the shape (k) and scale (c) parameters of the Weibull probability density function through four numerical methods, known as graphical method (GM), empirical method of Justus (EMJ), empirical method of Lysen (EML), and moment method (MM) in two distinct cities, Gravatá-PE and Osório-RS, under the influence of two wind regimes. To do that, it will be used the hourly wind data obtained through NASA’s Meteonorm database, from 2006 to 2015. Statistical analyzes also will be used to determine the best method used to determine these parameters.